Circular economy and rare materials: a challenge for the European countries - Paolo Pariso; Michele Picariello; Alfonso Marino (Entrepreneurship and Sustainability Issues, 2023)
The paper provides a knowledge increase of the circular economy model in the context of rare materials in Europe. Rare materials play a crucial role in various industries but are often associated with limited availability and environmental concerns. The paper highlights the importance of circular economy strategies in Europe to enhance the sustainable management and utilization of rare materials. It emphasizes the need for comprehensive policies, collaborative initiatives, and technological innovations to foster the transition towards a circular economy for rare materials in Europe. With the circular economy approach, Europe could minimize the environmental impact, reduce dependence on imports, and promote the sustainable use of rare materials, ultimately contributing to a more resilient and sustainable future.